Intracellular Thermal Probing Using Aggregated Fluorescent Nanodiamonds. Issue 3 (23rd November 2021) - Wu, Tianli; Chen, Xixi; Gong, Zhiyong; Yan, Jiahao; Guo, Jinghui; Zhang, Yao; Li, Yuchao; Li, Baojun
Abstract: Intracellular thermometry provides important information about the physiological activity of single cells and has been implemented using diverse temperature‐sensitive materials as nanoprobes. However, measuring the temperature of specific organelles or subcellular structures is challenging because it requires precise positioning of the nanoprobes. Here, it is shown that dispersed fluorescent nanodiamonds (FNDs) endocytosed in living cells can be aggregated into microspheres using optical forces and used as intracellular temperature probes. The aggregation of the FNDs and electromagnetic resonance between individual nanodiamonds in the microspheres lead to a sevenfold intensity enhancement of 546‐nm laser excitation. With the assistance of a scanning optical tweezing system, the FND microspheres can be precisely patterned and positioned within the cells. By measuring the fluorescence spectra of the microspheres, the temperatures at different locations within the cells are detected. The method provides an approach to the constructing and positioning of nanoprobes in an intracellular manner, which has potential applications in high‐precision and flexible single‐cell analysis. Abstract : Endocytosed fluorescent nanodiamonds (FNDs) dispersed in the cells are aggregated and positioned with high precision and flexibility by optical force. The aggregation of the FNDs and electromagnetic resonance between individual FNDs in the microspheres lead to a sevenfold intensity enhancement of 546‐nm laser excitation. The aggregated microspheres can be used as intracellular thermal probes for temperature detection of desired locations of the cells.